The effect of retro-cueing on an ERP marker of VSTM maintenance - Murray, A; Kuo, B; Stokes, M; Nobre, A (2009)
Previous research has found that Contralateral Delay Activity (CDA) is correlated with the number of items maintained in Visual Short Term Memory from one visual field (VF) (Vogel & Machizawa, 2004). CDA is usually elicited by a to-be-remembered array after a prospective cue (pro-cue) signalling the relevant side of the visual display, and is interpreted as a putative electrophysiological signature of WM maintenance. Attention can also be directed to the contents of VSTM, after the presentation of a visual array, using a retroactive cue (retro-cue) (Nobre, Griffin, & Rao, 2008). Because retro-cueing directs attention within a memory trace, potentially reducing the load of items to be maintained, we hypothesised that this would significantly attenuate the CDA. Participants were initially presented with a spatial pro-cue which reduced the number of to-be-remembered items to one side. After a delay, a memory array of either four (low load) or eight (high load) items was displayed. A retro-cue then cued participants to one location within the relevant VF, further reducing the load of to-be-remembered items; or provided no information, requiring participants to hold all items in the relevant VF. At the end of the trial, participants performed a same/different judgement on a test stimulus. Retro-cues significantly improved VSTM performance. Unexpectedly, the CDA was found to be abolished by the presentation of both spatially predictive and neutral cues, independently of the VSTM load participants had to maintain.